Runāto un dziedāto latviešu valodas patskaņu [ī], [ā] un [ū] kvalitātes salīdzinājums - Grigorjevs, Juris (Baltistica, 2011)
THE COMPARISON OF THE QUALITY OF SPOKEN AND SUNG LATVIAN VOWELS [i:], [ɑ:] AND [u:] Numerous studies in phonetics have attempted to investigate the differences between spoken and sung vowels. The majority of these studies dealt with the articulatory and acoustic changes observed in opera singers, however, there were several studies which compared the production of vowels by opera and choir singers. This article presents a pilot study performed on the basis of an audio material acquired from one informant (mezzo-soprano), where the acoustic quality of spoken Latvian vowels [i:], [ɑ:] and [u:] has been compared to the quality of the same vowels sung in isolation (in octave of La Minor, i.e., from A3 to A4, labeled in this article as octave of Do Major because of certain reasons) and sung in the verse of a song. It was observed during the current study that the transition from the chest register to the middle register had taken place between C4 and D4, which is normally observed in mezzo-sopranos. To make the interpretation of the influence of a variable pitch on the vowel formant pattern easier, all Latvian vowels were plotted in the psycho-physical F2ʹ/F1 (bark) plane. The observed changes in F1 reflect the tuning of the first vocal resonance to the pitch that is acquired by a jaw opening. Gradual larynx lowering and lip rounding can be the reason for lowering of F2ʹ value for [i:], reduced lip rounding — for increasing of F2ʹ value for [u:], but rising of the tongue tip — for increasing of F2ʹ value for [ɑ:]. The observed changes question the assumption that vowels in singing preserve their quality except for very low and very high registers (the octave under investigation does not belong to such registers). The minor differences observed in vowels sung in the verse from vowels sung in isolation can be explained by the influence of immediate phonetic context. It can be concluded that the data obtained in this investigation, in general, correspond to the findings of similar studies performed for other languages.